T-helper Type 17 and Regulatory T-cell Profiles in Renal Allograft Recipients with Calcineurin Inhibitor Toxicity - Ravi Shankar Kushwaha; Brijesh Yadav; Vikas Agarwal; Vinita Agarwal; Manoj Jain; Narayan Prasad (Indian Journal of Transplantation, 2025)
Introduction: The immune profiles of Th17 and Treg cells have been not studied in-depth in renal transplant recipients (RTRs) with calcineurin inhibitor toxicity (CNIT) till now. Therefore, we aimed to determine the Th17 and Treg cell profiles in RTRs with CNIT and stable graft function (SGF). Materials and Methods: A total of 40 RTRs with biopsy-proven CNIT (n = 30) and SGF (n = 10) RTRs were included in the study. A 10 ml of peripheral blood was collected and Th17 and Treg cell frequency, cytokines were analyzed by flow cytometry and enzyme-linked immunosorbent assay, respectively. A core of renal allograft biopsy was also collected, and intragraft mRNA transcript expression of retinoic acid-related orphan receptor C (RORC) (Th17) and FoxP3 (Treg) were analyzed by the reverse transcription-polymerase chain reaction. Results: The circulating frequency of Th17 cells were higher, and Treg cells were significantly lower in the CNIT group compared with SGF. The serum and peripheral blood mononuclear cell (PBMC) culture supernatant cytokines level of interleukin IL-17 and IL-6 remained higher in the CNIT group compared with SGF. The serum anti-inflammatory cytokines IL-10 and transforming growth factor β remained lower in CNIT. Similarly, the cytokine IL-10 level in PBMC culture supernatants was lower in CNIT. The intragraft injury scores of CNIT-associated lesions were significantly higher in the CNIT group. The intragraft mRNA transcript expression of both FoxP3 (Treg) and RORc (Th17) was significantly higher in the CNIT group compared to SGF. Conclusions: An increased ratio of Th17/Treg cells in circulating blood and intragraft mRNA transcript of RORC and FoxP-3 were observed in RTRs with CNIT. Th17 cells may be associated with the characteristics of stripped fibrosis of CNIT.